PENYULUHAN MANAJEMEN KEUANGAN DAN DIGITAL MARKETING PADA KELOMPOK JAMUR TIRAM “MANUT” - Yudha Alif Auliya; Dwi Wijonarko; Mohammad Zarkasi (Jurnal Transformasi Digital Masyarakat (DIGIMAS), 2026)
KPJT (Oyster Mushroom Farmers Group) Manut is a company consortium dedicated to the cultivation of oyster mushrooms and the processing of oyster mushroom products, situated in Klakah Village. KPJT Manut is a pioneer in the production of distinctive goods derived from processed oyster mushrooms, utilizing an empowerment-based business group model. Business units affiliated with KPJT can evolve into enduring commercial enterprises. Consequently, effective business development necessitates proficient finance and marketing management. This initiative aims to empower the business units of KPJT Manut, enabling them to effectively manage operations and ensure the sustainability of each unit. The techniques of implementation encompass field surveys, counseling, and monitoring and evaluation. The assessment results over one week indicated a 20% rise in demand for processed mushroom products following the implementation of digital marketing strategies.